2003
DOI: 10.1126/science.1089814
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Clustering of Dispersed tRNA Genes

Abstract: Early transfer RNA (tRNA) processing events in Saccharomyces cerevisiae are coordinated in the nucleolus, the site normally associated with ribosome biosynthesis. To test whether spatial organization of the tRNA pathway begins with nucleolar clustering of the genes, we have probed the subnuclear location of five different tRNA gene families. The results show that tRNA genes, though dispersed in the linear genome, colocalize with 5S ribosomal DNA and U14 small nucleolar RNA at the nucleolus. Nucleolar localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
269
4
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(292 citation statements)
references
References 25 publications
16
269
4
1
Order By: Relevance
“…In (i) a locus (triangle) is free to move within the circumference of the filled sphere; (ii) movement of the interaction points reduces the size of the sphere of movement relative to the anchor point effect, the ETS2 domain-retrotransposon element interactions exert a cis-effect which organizes the yeast chromosomes into loose domains and stabilizes other interactions. This model has implications for the separation of transcription by RNA polymerase I, II and III, given the association between repeated elements and PolIII genes (Kim et al, 1998), as originally proposed (Thompson et al, 2003). That repetitive sequences are involved in this genome organization fits with the domain model for DNA organization (Bodnar, 1988).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In (i) a locus (triangle) is free to move within the circumference of the filled sphere; (ii) movement of the interaction points reduces the size of the sphere of movement relative to the anchor point effect, the ETS2 domain-retrotransposon element interactions exert a cis-effect which organizes the yeast chromosomes into loose domains and stabilizes other interactions. This model has implications for the separation of transcription by RNA polymerase I, II and III, given the association between repeated elements and PolIII genes (Kim et al, 1998), as originally proposed (Thompson et al, 2003). That repetitive sequences are involved in this genome organization fits with the domain model for DNA organization (Bodnar, 1988).…”
Section: Resultssupporting
confidence: 58%
“…A standard curve is generated using a positive control and used to calculate the concentration of the samples based on the cycle at which they cross the critical threshold (Ct). Samples are typically run in triplicate or quadruplicate by fluorescent in situ hybridization, to cluster with the 5S rRNA (Thompson et al, 2003). Since Ty elements are typically within 750 bp of tRNA genes (Kim et al, 1998), this is further evidence indicating that Ty elements cluster together in the vicinity of the ETS2 domain, which is adjacent to the 5S rRNA gene.…”
Section: S 25s Its1 and It2 Rrnas) Mspi Restriction Sites Are Depmentioning
confidence: 99%
“…Namely, tRNA genes play an important role in genomic organization, as they are recruited to the nucleolus in wild type cells (Thompson et al, 2003) and thus should become more dispersed in ErDNA nuclei. Probably due to this recruitment (Thompson et al, 2003), tRNA genes showed increased condensin occupancy (as compared to other IGRs) in wild type: 20% of 241 tRNA genes analyzed in coincided with condensin peaks. However, in ErDNA strain ChIP-chip analysis 15% of 262 analyzed tRNA genes were still condensin-enriched (Supplement 1), indicating that this aspect of intranuclear chromosome packaging did not change significantly in ErDNA cells.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms by which Mot1, Rpa49 and Rrn3 influence tRNA biogenesis is unclear, but it is possible that they indirectly influence the process through their involvement in Pol I transcription. Transcription of tRNA genes as well as 5´-end processing of pre-tRNAs has been reported to localize to the nucleolus [4749]. Moreover, dissociation of pre-tRNA from the nucleolus and defects in 5´ end processing have been observed in cells defective in Pol I transcription or rRNA processing [50,51].…”
Section: Discussionmentioning
confidence: 99%